2022
DOI: 10.35188/unu-wider/2022/229-4
|View full text |Cite
|
Sign up to set email alerts
|

Pension funds in sub-Saharan Africa

Abstract: This study has been prepared within the UNU-WIDER project The domestic savings shortfall in developing countries-what can be done about it? which is part of the Domestic Revenue Mobilization programme. The programme is financed through specific contributions by the Norwegian Agency for Development Cooperation (Norad).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…They recommend that countries should make pension policies that are geared towards institutionalizing savings. On the contrary, Nyang'oro and Njenga [38] examined pension fund in sub-Saharan Africa and found that the pension system is characterized by low participation, low income levels, low returns due to investments only in government securities, low asset under management and restrictive regulations. They propose that a targeted universal pension system (to be financed using public resources) should be instituted.…”
Section: The Intermediation Theory By Gurley and Shawmentioning
confidence: 99%
“…They recommend that countries should make pension policies that are geared towards institutionalizing savings. On the contrary, Nyang'oro and Njenga [38] examined pension fund in sub-Saharan Africa and found that the pension system is characterized by low participation, low income levels, low returns due to investments only in government securities, low asset under management and restrictive regulations. They propose that a targeted universal pension system (to be financed using public resources) should be instituted.…”
Section: The Intermediation Theory By Gurley and Shawmentioning
confidence: 99%
“…Regulatory changes in Nigeria, such as the Regulation of Pension Fund Assets in 2006, have allowed pension funds to increase assets under management National Pension Commission, 2006), reaching USD 32.3 billion in 2020(OECD, 2021b. Ghanaian pension funds have also grown steadily, accumulating USD 4.7 billion as of 2021, making Ghana the second-largest pension fund market in the region (Nyang`oro and Njenga, 2022;OECD, 2021b). The Nigerian Sovereign Wealth Authority had USD 3 billion in assets under management in 2021, the highest amount of any sovereign wealth fund in West Africa.…”
Section: The Allocation Of Sustainable Investments Is Skewed Towards ...mentioning
confidence: 99%
“…Au Nigéria, des changements réglementaires, notamment la réglementation des actifs des fonds de pension en 2006, ont permis à ceux-ci d'augmenter leur enveloppe d'actifs sous gestion National Pension Commission, 2006), qui atteignait ainsi 32.3 milliards USD en 2020 (OCDE, 2021b). Au Ghana, les fonds de pension ont également connu une croissance régulière, avec un cumul de 4.7 milliards USD en 2021, portant le pays au rang de deuxième marché de fonds de pension de la région (Nyang`oro et Njenga, 2022 ;OCDE, 2021b). La Nigerian Sovereign Wealth Authority (Fonds souverain nigérian) disposait en 2021 de 3 milliards USD d'actifs sous gestion, le montant le plus élevé de tous les fonds souverains d'Afrique de l'Ouest, suivie du Fonds souverain d'investissements stratégiques du Sénégal (FONSIS) et du Ghana Heritage Fund, à respectivement 0.8 et 0.7 milliard USD d'actifs sous gestion (SWFI, n.d.).…”
Section: Les Obstacles à La Monétisation Des éCosystèmes Naturelsunclassified